KEBERAGAMAN BUDAYA SIDOARJO DALAM PEMBELAJARAN: PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Ike Kumala Sari , Hanidah Amilia Sholehah; Julia Fatimatur Rahmawati , Muhammad Nur Hidayatullah; Nur Latifah Agustina, Princeski Cahya Pertiwi , Cholifah Tur Rosidah; Bagus Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to increase student learning motivation by utilizing Sidoarjo cultural diversity in learning by using Culturally Responsive Teaching (CRT) approach. The method used in this research is Classroom Action Research (PTK) which is carried out in several cycles to obtain optimal results. Data collection techniques using questionnaires, observation, and documentation techniques. The data analysis technique used in this research is qualitative description. The research subjects were students of class IV B SDN Kepuhkiriman 1 Sidoarjo with a total of 28. The results showed that there was an increase in learning motivation. This is shown from the results of questionnaires and observations. The increase in the five aspects of learning motivation from the questionnaire results obtained an average percentage of learning motivation of 61.6% in the “sufficient” category in the pre-cycle, 73.9% in cycle I in the ‘good’ category and 90.3 in the “very good” category in cycle II. Then from the observation results obtained an average presentation of 77.68% in the “good” category in cycle I and 88.4% in the “very good” category in cycle II.